Operation control method and device of cleaning equipment, storage medium and electronic equipment - YAN GUIXIANG; ZHENG YUE (2023)
The embodiment of the invention provides an operation control method and device of cleaning equipment, a storage medium and electronic device.The method comprises the steps that specified electrical attributes of the outer surface of a cleaning part of the cleaning equipment are detected through a preset detection component, and a target attribute value is obtained, the specified electric attribute is used for identifying the smudginess degree of the outer surface of the cleaning piece; based on the corresponding relation between the preset attribute value range of the specified electrical attribute and the cleaning solution proportion, a target proportion matched with the target attribute value is set, the cleaning solution proportion is the proportion of clean water of the cleaning equipment and cleaning solution of the cleaning equipment, and the proportion of the clean water and the cleaning solution is in negative correlation with the smudginess degree of the outer surface of the cleaning piece; the clea